The preventive effect of sodium-glucose co-transporter-2 inhibitors on atrial fibrillation and atrial flutter in patients with chronic kidney disease: a meta-analysis - Yang, Qian; Wang, Chen; Wang, Wenjing; Li, Yanhong; Dang, Yi (Frontiers in Pharmacology, 2025)
BackgroundThe presence of atrial fibrillation (AF) and atrial flutter (AFL) in patients with chronic kidney disease (CKD) can exacerbate renal dysfunction, which in turn increases the onset of AF or AFL. Sodium-glucose co-transporter-2 inhibitors (SGLT2i) have been proven to have cardiac and renal protective effects. The meta-analysis was performed to investigate whether SGLT2i can reduce the risk of AF/AFL in patients with CKD.MethodsPubMed, Embase, Cochrane Library, and Clinical Trials.gov were searched up to December 2024. Randomized controlled trials (RCTs) comparing of SGLT2i and placebo on AF/AFL in patients with CKD were included. Risk ratio (RR) with 95% confidence interval (CI) were calculated in the overall population and selected subgroups.Results10 RCTs involving 28,712 patients were included. SGLT2i significantly reduced the risk of the composite events of AF and AFL in patients with CKD (0.65% vs. 0.91%; RR 0.73, 95% CI 0.56-0.95, P = 0.02) in overall population, but did not reduce the risk of AF (0.56% vs. 0.75%; RR 0.76, 95% CI 0.57-1.01, P = 0.06) or AFL (0.097% vs. 0.17%; RR 0.58, 95% CI 0.30–1.13, P = 0.11). Subgroup analysis based on sample size and follow-up duration showed that SGLT2i reduced the risk of AF in trials with sample size more than 1,000 and follow-up duration longer than 2 years (0.59% vs. 0.80%; RR 0.74, 95% CI 0.55–0.99, P = 0.04). Subgroup analysis based on different populations showed that SGLT2i reduced the risk of AF in patients with CKD (partial without diabetes) (0.48% vs. 0.90%; RR 0.53, 95% CI 0.33–0.85, P = 0.009), while had no effect on AF in patients with both diabetes and CKD. Subgroup analysis based on different types of SGLT2i showed that only empagliflozin reduced the risk of AF compared to placebo (0.51% vs. 0.94%; RR 0.55, 95% CI 0.31–0.96, P = 0.04).ConclusionSGLT2i could reduce the risk of the composite events of AF and AFL in patients with CKD, and also could reduce the risk of AF in trials with large sample size and long follow-up duration.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251053244.